P87 Single centre experience of nebulised magnesium sulphate in severe acute paediatric wheeze. (December 2018) - Forbes, M; Langley, RJ; Macleod, KA
Abstract : Introduction: Nebulised Magnesium Sulphate (MgSO4) is proposed as an effective treatment for acute wheeze in children however its use is not widely established due to conflicting results in published studies. Combination nebulisers containing MgSO4 were introduced as a new therapy in our centre in 2016 as part of a local wheeze guideline for hypoxic patients (Sp02 <92%) with severe symptoms following inhaled salbutamol multidosing. The aim of this study is to observe differences in outcomes from before and after the introduction of MgSO4 combination nebulisers. Methods: Medical records were reviewed for all admissions to RHSC with wheeze attack during the month of November. Data on patient demographics, initial observations, first treatment received and subsequent management were analysed. These results were then compared with a similar data set collected from November 2015, the only difference in management protocol being the introduction of nebulised MgSO4. Results: 110 children (age 2–16 years) were admitted with acute wheeze in November 2016. 32% were hypoxic on arrival (SpO2 <92%). 75 (68.2%) patients received inhaled salbutamol multidosing as first-line management as recommended in the guideline. Nebulised MgSO4 was given as first-line management without prior multidosing in 21 (19.1%) cases. A further 14 patients (12.7%) received another nebulised agent. Treatment with nebulisers did not often correspond to those who were hypoxic on arrival. Compared with 2015 data, prior to introduction of MgSO4 nebulisers, there was an absolute reduction in use of IV MgSO4 (14.0% vs 9.1%) and aminophylline (5.2% vs 1.8%) (table 1). There was no real difference in inpatient stay (1.74 vs 1.84 days) or rate of admission to high dependency/intensive care (5.2% vs 6.4%). Conclusion: With the introduction of nebulised MgSO4 combination treatment, administration of IV medications was reduced. Length of stay and HDU/PICU admissions did not change. Further analysis is needed to determine whether this is maintained. This study indicates that combination nebulisers containing MgSO4 can be introduced into an acute wheeze guideline, but further work is required to understand the effect of nebulised MgSO4 on escalation of treatment and to limit use to those who are most likely to benefit.